ANALISIS KETERAMPILAN MENYIMAK MELALUI PENDEKATAN SAINTIFIK PADA ANAK KELAS IV DI SD NEGERI 6 REJANG LEBONG - Febi Sinta (SCHOLASTICA JOURNAL JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2022)
In listening skills through a scientific approach, students must understand and develop the four aspects of listening skills, namely, speaking, reading, listening, and writing which must be mastered after we undergo the process of learning to listen. So a scientific approach is needed to analyze the level of students' ability in listening skills through a scientific approach. The purpose of this study was to determine the ability of students in listening skills through a scientific approach for class IV SD Negeri 6 Rejang Lebong, the research method used was descriptive qualitative, research data sources: interviews, LKPD documentation. Research data analysis analysis techniques: data reduction, data presentation, conclusion drawing. The results of this study are: Students who fall into the very good category. totaling 15 students or as much as 57.70%, students belonging to the good category totaled students or as many as 19.2%, there were students who were included in the sufficient category totaling 2 or as much as 7.6%, there were 3 students who entered the less category or as much as 15.40%, and none of the students included in the failed category.